A chimeric protein composed of the binding domains of Clostridium perfringens phospholipase C and Trueperella pyogenes pyolysin induces partial immunoprotection in a mouse model. (August 2016) - Hu, Yunhao; Zhang, Wenlong; Bao, Jun; Wu, Yuhong; Yan, Minghui; Xiao, Ya; Yang, Lingxiao; Zhang, Yue; Wang, Junwei
Abstract: Trueperella pyogenes and Clostridium perfringens are two kinds of conditional pathogens frequently associated with wound infections and succeeding lethal complications in various economic livestock. Pyolysin (PLO) and phospholipase C (PLC) are the key virulence factors of these two pathogens, respectively. In our study, a chimeric protein called rPC-PD4, which is composed of the binding regions of PLO and PLC, was synthesized. The toxicity of rPC-PD4 was evaluated. Results revealed that rPC-PD4 is a safe chimeric molecule that can be used to develop vaccines. Immunizing BALB/c mice with rPC-PD4 induced high titers of serum antibodies that could efficiently neutralize the hemolytic activity of recombinant PLO and PLC. After the challenge with T. pyogenes or C. perfringens was performed through the intraperitoneal route, we observed that rPC-PD4 immunization could provide partial immunoprotection and reduce lung, intestine, and liver tissue damage to mice. This work demonstrated the efficacy of the rationally designed rPC-PD4 chimeric protein as a potential vaccine candidate against C. perfringens and T. pyogenes . Highlights: A new chimeric protein rPC-PD4 composed of binding domains of phospholipase C and pyolysin was constructed. The safety of the chimeric protein is better than any of the two parts comporise of it. The rPC-PD4 could elicit partial immunoprotection against Clostridium perfringens and Trueperella pyogenes .